Women in managerial positions in Europe: Focus on Germany - Elke Holst (Management Revue, 2006)
Prejudices and stereotypical beliefs about the role of women in society often limit their chances of reaching top leadership positions. This paper presents a detailed analysis of the socio-economic structure and the gender pay gap in managerial positions in Germany building on a review from a cross-national perspective of women's progress to high-ranking positions and of initiatives to overcome the 'glass ceiling'. Suggestions are made for improving the situation of women in order to permit more balanced gender participation in the economy, while also promoting national competitiveness and higher levels of wellbeing for the society.
Keywords: 650; women in management; “glass ceiling”; socio-economic structure; horizontal and vertical segregation; gender pay gap; diversity awareness; Weibliche Führungskräfte; Lohndifferenzierung; EU-Staaten; Deutschland